Grammatical deviations as features of Philippine English in local newspaper editorials - Cavanliit, Kenneth Louis (2022)
This study identified the grammatical features of Philippine English in local newspaper editorials. Specifically, the study determined the frequency of occurrence of deviant cases in terms of subject-verb agreement, articles, and prepositions. Through non-probability sampling, a total of forty-five (45) editorials were retrieved from the websites of three local newspapers and were interpreted and analyzed to identify grammatical deviations. To ensure the validity of the deviations found in the editorials, the researcher, along with three grammar raters, verified all the texts that contained the grammatical deviations. The specifics of the frequency counts showed that most of the deviations in subject-verb agreement were due to the use of a special noun (collective, clausal), while most of the deviant cases in article usage were associated with a missing definite article. For preposition usage, most of the deviations were linked to a missing preposition. Grammatical deviations as features of Philippine English in local newspaper editorials is a manifestation that a certain variety of English can be used as a medium to relay information and influence people’s opinions within a specific context.
Keywords: Newspapers